Tantangan Santri Baru dalam Menyikapi Perbedaan Jadwal Sekolah dan Pondok Pesantren di Pamekasan - Moh. Hariri; Heni Listiana; Mohammad Suhud (Departement of Mathematics Education, 2024)
This article discusses the adjustments that new students at the Islamic boarding school must make after losing 53 days of study time. This delay is caused by their need to wait for their final exams at their previous schools due to differences between the boarding school’s academic calendar and the government’s academic calendar. This situation creates a dilemma for these students, who need to catch up on the lessons from the beginning of the books they missed. The research uses a qualitative approach with descriptive analysis at the Miftahul Ulum Bettet Islamic Boarding School in Pamekasan. To address this issue, the school administration seeks solutions, including(1) Conducting special tests for new students to assess their basic knowledge of religious studies.(2) Creating special classes for new students to ensure they start learning from the beginning of the books.(3) Combining classes with existing students while providing additional guidance to new students on the lessons they missed. Supervision, direction, and coordination from the boarding school administrators, formal school managers, and the students’ guardians are highly encouraged to support the education of the new students, who come from various different backgrounds.